Моделирование методом конечных элементов металлургических и термодеформационных процессов при упрочняющей плазменной наплавке - Земмлер, У.; Алалусс, К.; Маттес, К.-Й. (Автоматическая сварка, 2005)
Изучен процесс плазменной наплавки дугой прямого действия (РТА) твердых износостойких (сплавов V12 и V18 на основе ванадия на основной металл - конструкционную сталь S35J0. Различия в термомеханических свойствах, локальных термопластических деформаци х и фазовых превращениях материалов могут вызвать высокие остаточные напряжения и деформации. Сравниваются результаты моделирования с измерениями распределения температуры и деформации. Проверенные и улучшенные модели на основе конечных элементов можно использовать для изучения влияния параметров сварки на деформации и остаточные напряжения с целью оптимизации сварных изделий. The paper deals with the process of plasma transferred arc (PTA) deposition of thick hardfacing layers (vanadium-based alloys V12 and V18) on the base material (structural steel S355J0). The differences in the thermo-mechanical properties, local thermo-plastic deformations and phase transformations may cause high residual stress and distortion. The transient thermo-elastic-plastic behaviour of the PTA material deposition is investigated by means of the 3D Finite Element Method (FEM). All thermo-mechanical parameters are dependent on the temperature. The simulated results are compared with measurements of temperature distribution and distortions in order to increase the quality of the numerical models. Using the verified and improved FE-models one can study the influence of welding parameters on the deformations and residual stresses with the aim to optimize the weldments. For thick deposit layers the austenite-martensite transformations have a significant influence on the residual stresses and distortions. Technical applications are shown.